Competitive spreading of different ideas : a simulation study - Wang, Yajie (2017)
Competitions between different ideas widely exist in social systems. In this dissertation, we study on spreading dynamics of multiple competing ideas in complex networks, mainly by conducting extensive simulations on a few popular synthetic network models. Specifically, we introduce an S-I-H model where individuals holding an idea may lose the enthusiasm and capabilities to spread out the idea after a certain period of time, while they may still keep certain levels of resistances to other ideas. It is interesting to evaluate whether and how the reduced enthusiasm/capability of idea spreading after the enthusiastic time may affect system dynamics. We also assess the effects of a few factors, e.g., transmissibility and resistance levels, initial infection size, etc., by testing on some different cases with different parameter values. A few interesting observations have been made.